Variation orders in construction contract - Sikan, Hashim (Universiti Teknologi Malaysia, 1999)
This paper attempts to examine the provision of clauses on variations in the standard forms of contract commonly used in the local construction industry i.e. the PWD Form 203 for building and civil engineering works in the public sector, the PAM Form for building and the IEM Form for the civil engineering works both in the private sector. It touches all aspects of variationsi both academically and in practice especially on the need to have variation clauses in the contract, its definition, application and more importantly the method of pricing. This could be something different from what has been encountered during the practical application on site. It also explains why adherence to the terms of contract in the contract administration especially on the pricing and payment will benefit both parties in a long run